Mobiliti Buruh Antara Industri : Kajian Kes Di Kawasan Perindustrian Mergong , Alor Setar, Kedah Darul Aman - Zuriah, Sulaiman (2002)

(untitled)
This study attempts to identify the important factors that influence the labor mobility in the Mergong Industrial Area. Five establishments were chosen as the unit of analysis and 310 respondents; were selected to complete the questionnaires. However, only 255 respondents gave complete answers. Data was collected using a structured questionnaire. The result showed that six factors; " educations, skills, information, wage, marital status and transportation " to be significantly related to Labor mobility in Mergong lndustrial Area. Medical benefit provided by the employer is the most important factor in contributing to the labor mobility, followed by three other significant factors; facilities in terms of transportation, facilities in term of accommodation and food provided.